The Rise and Fall of the Femme Fatale in British Literature, 1790-1910. - Braun, Heather L. (Fairleigh Dickinson, 2012)
The Rise and Fall of the Femme Fatale: From Gothic Ghosts to Victorian Vamps explores the femme fatale's career in nineteenth-century British literature. It traces her evolution-and devolution-formally, historically, and ideologically through a selection of plays, poems, novels, and personal correspondence. Considering well-known fatal women alongside more obscure ones, this study sheds new light on emerging notions of gender, sexuality, and power throughout the long nineteenth century.